Rancang Bangun Web SUWUNGCV - Fahrudin, Imam; Abdurrahman Hakim, Nurfadhli; Purnama Sari, Sri; Kurnia Sari, Ina; Bambang Sumantri, R Bagus (STMIK Komputama Majenang, 2021)
CV is a curriculum vitae that contains a summary of a person's educational journey and professional activities. Curriculum vitae serves as a self-indicator which includes history, experience, talents and abilities, usually intended to apply for a job. CV is indeed familiar to everyone, even so there are still many people who are confused in making CVs and there are still many people who are lazy to make CVs manually. In this era of globalization, we can take advantage of internet services, one of which is a website. A website is an interconnected web page containing a collection of information provided individually, in groups or organizations. Based on this description, the